Rice lipid transfer protein, OsLTPL23, controls seed germination by regulating starch-sugar conversion and ABA homeostasis - Li, Quanlin; Zhai, Wenxue; Wei, Jiaping; Jia, Yanfeng (Frontiers in Genetics, 2023)
Seed germination is vital for ensuring the continuity of life in spermatophyte. High-quality seed germination usually represents good seedling establishment and plant production. Here, we identified OsLTPL23, a putative rice non-specific lipid transport protein, as an important regulator responsible for seed germination. Subcellular localization analysis confirmed that OsLTPL23 is present in the plasma membrane and nucleus. The knockout mutants of OsLTPL23 were generated by CRISPR/Cas9-mediated genome editing, and osltpl23 lines significantly germinated slower and lower than the Nipponbare (NIP). Starch and soluble sugar contents measurement showed that OsLTPL23 may have alpha-amylase inhibitor activity, and high soluble sugar content may be a causal agent for the delayed seed germination of osltpl23 mutants. Transcript profiles in the germinating seeds exhibited that the abscisic acid (ABA)-responsive genes, OsABI3 and OsABI5, and biosynthesis genes, OsNCED1, OsNCED2, OsNCED3 and OsNCED4, are obviously upregulated in the osltpl23 mutants compared to NIP plants, conversely, ABA metabolism genes OsABA8ox1, OsABA8ox2 and OsABA8ox3 are stepwise decreased. Further investigations found that osltpl23 mutants displays weakened early seedling growth, with elevated gene expresssion of ABA catabolism genes and repressive transcription response of defence-related genes OsWRKY45, OsEiN3, OsPR1a, OsPR1b and OsNPR1. Integrated analysis indicated that OsLTPL23 may exert an favorable effect on rice seed germination and early seedling growth via modulating endogenous ABA homeostasis. Collectively, our study provides important insights into the roles of OsLTPL23-mediated carbohydrate conversion and endogenous ABA pathway on seed germination and early seedling growth, which contributes to high-vigor seed production in rice breeding.